Right Thoughts at the Last Moment: Buddhism and Deathbed Practices in Early Medieval Japan, by Jacqueline Stone. (30th December 2018) - Astley, Ian
Abstract : Right Thoughts at the Last Moment: Buddhism and Deathbed Practices in Early Medieval Japan, by Jacqueline Stone. Kuroda Institute studies in East Asian Buddhism 26. University of Hawai'i Press: 2016. 624pp; illustrated, incl. 11 colour plates, 1 B&W illustration. Hb. $68.00 (cloth). ISBN-13: 9780824856434.